Artificial intelligence for knowledge management : second IFIP WG 12.6 International Workshop, AI4KM 2014, Warsaw, Poland, September 7-10, 2014, revised selected papers /: second IFIP WG 12.6 International Workshop, AI4KM 2014, Warsaw, Poland, September 7-10, 2014, revised selected papers. (2015) - Unknown
No abstract available